2000
DOI: 10.2337/diacare.23.12.1811
|View full text |Cite
|
Sign up to set email alerts
|

Risk of nephropathy can be detected before the onset of microalbuminuria during the early years after diagnosis of type 1 diabetes.

Abstract: Abbreviations: ACR, albumin-to-creatinine ratio; AER, albumin excretion rate; CV, coefficient of variation; ELISA, enzyme-linked immunosorbent assay; HPLC, high-performance liquid chromatography; IQ, interquartile; MA, microalbuminuria; ORPS, Oxford Regional Prospective Study.A table elsewhere in this issue shows conventional and Système International (SI) units and conversion factors for many substances.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
55
0
1

Year Published

2001
2001
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(62 citation statements)
references
References 21 publications
4
55
0
1
Order By: Relevance
“…Borderline microalbuminuria at first complication assessment more than doubled the risk of persistent microalbuminuria compared with normoalbuminuria, and the effect persisted after adjusting for duration. This confirms previous studies in which early elevation of AER and the rate of rise of albumin-to-creatinine ratio within the normal range were predictors for microalbuminuria (8,29). While this could be explained by genetic predisposition to nephropathy (30 -32), it argues for the possibility of intervention at a lower level of albuminuria than current guidelines recommended for adolescents (21).…”
Section: Biochemical Subanalysissupporting
confidence: 71%
“…Borderline microalbuminuria at first complication assessment more than doubled the risk of persistent microalbuminuria compared with normoalbuminuria, and the effect persisted after adjusting for duration. This confirms previous studies in which early elevation of AER and the rate of rise of albumin-to-creatinine ratio within the normal range were predictors for microalbuminuria (8,29). While this could be explained by genetic predisposition to nephropathy (30 -32), it argues for the possibility of intervention at a lower level of albuminuria than current guidelines recommended for adolescents (21).…”
Section: Biochemical Subanalysissupporting
confidence: 71%
“…Although MA was transient in some of the cases in our study, we recently reported that subjects with persistent MA (2 consecutive years) and transient MA (1 year only) may be at a similar risk of diabetic renal damage, as estimated by the rate of increase of albumin excretion in the years before MA onset (19). Therefore, if a higher systemic BP were important in early renal damage, then the inclusion of subjects with both transient and persistent MA as cases should not have affected the power of our study to detect a BP difference before MA onset.…”
Section: Methodsmentioning
confidence: 90%
“…But in children and young adults, albuminuria and overt nephropathy are relatively uncommon. Moreover, several recent studies have reported that microalbuminuria is sometimes reversible (13,19,23). With the exception of one small study (22), the effect of age at onset of diabetes on earlier stages of nephropathy has not been previously reported because investigators have heretofore lacked renal morphometric measures to detect these earlier stages.…”
mentioning
confidence: 88%